Relationship between patient and physician-rated xerostomia and dose distribution to the oral cavity and salivary glands for head and neck cancer patients after radiotherapy. (3rd October 2019) - Kaae, J. K.; Johnsen, L.; Hansen, C. R.; Kristensen, M. H.; Brink, C.; Eriksen, J. G.
Abstract: Introduction: Xerostomia is a frequent complication after curative intended radiotherapy (RT) for head and neck squamous cell carcinoma (HNSCC). Assessment of xerostomia is commonly done by the physician. The aim of this study is to investigate the relation between patient and physician-rated xerostomia and to predict the degree of xerostomia from patients with self-reported xerostomia based on delivered doses to the oral cavity, parotid, and submandibular glands. Material and methods: During a 2-year period, consecutive HNSCC patients attending the follow-up clinic were included. All included patients had self-reported xerostomia, and completed the disease-specific EORTC QLQ-H&N35 questionnaire. The physician assessed the degree of xerostomia with the DAHANCA toxicity scale and was blinded for the EORTC score. Oral cavity, parotid, and submandibular glands (OAR) were delineated on the planning CT according to international guidelines. DVH were extracted from treatment plans. Logistic regression tested the relation between mean doses, patient characteristics, and xerostomia scores. Differences between DVH values and scoring of xerostomia were analyzed with a Kruskal–Wallis test. The relation between xerostomia and dose distributions was further investigated using principal component analysis (PCA). Results: In total, 109 patients were included in the study. A weak correlation was seen between patient and physician-rated toxicity ( p  = .001), however, in general patients reported more toxicity than physicians. For EORTC score ≥2, the multi-variable analysis was significant for doses to the oral cavity, tobacco status and use of xerogenic medication. Neither the DVH analysis nor the PCA found any clear distinction between xerostomia scores for EORTC or DAHANCA and investigated OARs. Conclusion: Patients tended to report higher scores of xerostomia than the physician. PCA indicated a complex relation between doses to the OAR and xerostomia scores, showing e.g., that reducing doses in one organ was on the expense of increased dose to another organ.